The design and synthesis of an antibacterial phenothiazine–siderophore conjugate - Tarapdar, Abed (Beilstein J Org Chem, 2018)
Siderophore–antibiotic conjugates consist of an antibiotic covalently linked by a tether to a siderophore. Such conjugates can demonstrate enhanced uptake and internalisation to the bacterial cell resulting in significantly reduced MIC values and extended spectrum of activity. Phenothiazines are a class of small molecules that have been identified as a potential treatment for multidrug resistant tuberculosis and latent TB. Herein we report the design and synthesis of the first phenothiazine–siderophore conjugate. A convergent synthetic route was developed whereby the functionalised phenothiazine component was prepared in four steps and the siderophore component also prepared in four steps. In M. smegmatis the functionalised phenothiazine demonstrated an equipotent MIC value in direct comparison to the parent phenothiazine from which it was derived. The final conjugate was synthesised by amide bond formation between the two components and global deprotection of the PMB protecting groups to unmask the catechol iron chelating groups of the siderophore. The synthesis is readily amenable to the preparation of analogues whereby the siderophore component of the conjugate can be modified. The route will be used to prepare a library of siderophore–phenothiazine conjugates for full biological evaluation of much needed new antibacterial agents.